Thinking Processes of Mentally retarded: Students Disabled at Junior High School in Solving Fractions Problems - Irwan Akib; Andi Husniati; Fitri Kusumah; Kristiawati Kristiawati; Suritno Fayanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the thinking processes of students with special needs through three stages of thinking, namely the formation of understanding, the formation of opinions, and the conclusion of solving fraction problems. This research is a qualitative descriptive study with the research subject being a male student with mild mental retardation. The data analysis method was made in the form of data triangulation, which aims to test the wetness of the data. From the results of the analysis, it was found that the thinking processes involved in solving fractional problems by mentally disabled male students (1) involve the formation of understanding and can form understanding thru their thinking processes; (2) at the opinion formation stage, they need direction to be able to determine what strategies or methods will be used in solving problems.